Mediation effect of perceived learning in the relationship between institutional factors and the level of course satisfaction in distance learning - Amoozegar, Azadeh; Mohd Daud, Shaffe; Mahmud, Rosnaini; Ab. Jalil, Habibah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Acknowledging that distance learning dramatically increased in the past 20 years: on-line course retention and the continual participation of students in the same course; remains a significant challenge. In this case, identification of factors, which contribute to student satisfaction and experience from distance learning has become an important issue among on-line educators. Institutional factors in terms of support were found to be the key factors in students’ satisfaction. The aim of this paper was to investigate the contribution of institutional factors toward course satisfaction in distance learning environment. This study was conducted in two Malaysian Research Universities among 367 undergraduate distance students. The quantitative data are based on student evaluation forms: their evaluation of university support, administrative support, technical support, and the overall course satisfaction. The result of the study revealed that institutional factor was a significantly positive, and strong factor associated with level of course satisfaction.